2007
DOI: 10.1580/06-weme-or-013r.1
|View full text |Cite
|
Sign up to set email alerts
|

Mountain Sickness Knowledge Among Foreign Travelers in Cuzco, Peru☆

Abstract: This survey adds to the body of knowledge that indicates a lack of AMS knowledge among travelers. In addition, this survey identifies 2 potential avenues for improved dispersal of information: 1) guidebooks for countries of concern and 2) national health agency Web sites linked to information on pretravel vaccinations. Recommendations are made to utilize these commonly accessed resources to increase AMS information distribution to the general populous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 7 publications
4
24
0
Order By: Relevance
“…A recent study evaluated mountain sickness knowledge among foreign travelers in Cuzco, Peru and found that only 9% of the subjects in this study knew about acetazolamide as prophylaxis for or treatment of AMS. 13 Limitations of our study are those inherent in many similar field studies. Selection bias may have affected our results, as a portion of the 74 subjects lost to follow-up may have failed to complete the study due to AMS symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study evaluated mountain sickness knowledge among foreign travelers in Cuzco, Peru and found that only 9% of the subjects in this study knew about acetazolamide as prophylaxis for or treatment of AMS. 13 Limitations of our study are those inherent in many similar field studies. Selection bias may have affected our results, as a portion of the 74 subjects lost to follow-up may have failed to complete the study due to AMS symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Other studies also report deficits in wilderness medical knowledge. [10][11][12] Kuepper et al administered a 17question survey regarding wilderness medical knowledge to 283 mountaineers in the Swiss Alps and found 58.1% of answers to be correct. 12 Researchers concluded that this cohort performed poorly.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Meritt et al found that 58% of participants could identify 2 or fewer symptoms of acute mountain sickness. 11 Recognition of these symptoms is particularly important given that rates of altitude illness range from 28% to 34% of on peaks 44000 meters (13,123 feet). 7 Like the Campbell et al study, we are able to report that medical training is associated with higher medical knowledge scores.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have examined the correlation between medical training with general hiker preparedness, [5,6] but none has linked training with levels of preparedness or preparedness for altitude exposure. Medical training may have an impact on altitude preparedness through potentially increased awareness of the physiological changes involved in altitude sickness.…”
Section: Introductionmentioning
confidence: 99%